Evaluasi Program Pembelajaran PJOK Yang Berorientasi Hots Di Sekolah Kecamatan Lubuk Pakam Tahun Ajaran 2022-2023 - Syahbandi, Fahmi; Irfan, Muhammad; Siregar, Samsuddin; Sinulingga, Albadi; Simatupang, Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research evaluates the HOTS-oriented PJOK learning program in Lubuk Pakam sub-district schools. This research is a mixed methods research, namely a research step combining two forms of research approaches: qualitative and quantitative. This research includes observations, questionnaires, interviews, and documentation regarding school data collection methods. The research found that the context indicators for school principals, teachers, and deputy principals were outstanding. In contrast, the input indicators in this research were in the very good category for principals, teachers, and deputy principals. This process indicator is in the